Pengaruh Brand Image Dan Kualitas Produk Terhadap Minat Beli Produk Hp Samsung - Elsa Irfayati; Asri Rejeki (Universitas Muhammadiyah Gresik, 2026)
Objective: This study aims to empirically examine the influence of brand image and product quality on the purchase intention of Samsung smartphones among millennials. Brand image in this research includes three dimensions: mystery, sensuality, and intimacy. Meanwhile, product quality is measured through six dimensions: performance, reliability, features, durability, conformance quality, and style. Purchase intention consists of transactional, referential, preferential, and exploratory dimensions. This research employed a quantitative approach with a correlational design. Method: The sampling technique used was non-probability sampling with an incidental sampling method, involving 69 respondents who are millennial users of Samsung smartphones at Universitas Muhammadiyah Gresik. Data were collected using three scales: brand image, product quality, and purchase intention—developed based on relevant theories and tested for validity and reliability. Data analysis was conducted using multiple linear regression. Result: . The results showed that brand image and product quality simultaneously have a significant effect on purchase intention (F = 79.588; p < 0.05). Partially, brand image significantly influences purchase intention (t = 4.226; p < 0.05), as does product quality (t = 8.277; p < 0.05). The adjusted R square value of 0.585 indicates that 58.5% of the variance in purchase intention can be explained by brand image and product quality. Conclusion: These findings suggest that a strong brand image and high perceived product quality can enhance millennials' intention to purchase Samsung smartphones.